Okoljska globalizacija, nosilnost okolja in gospodarski razvoj - Plut, Dušan (Naše gospodarstvo, 2008)
Due to the increase in the world population and, consequently, in the use of natural resources per capita, environmental pollution assumed planetary dimensions towards the end of the 20th century. In several cases material activity of humankind exceeds the global carrying capacity of the environment, and the desired rise in material welfare is accompanied by the exhausting of environmental resources and the lowering of environmental quality. The geographic space has assumed a new i. e. ecosystem, dimension. The extent and way of its functioning should also be integrated by the economy. The world economy, as one of the constituents of the global environment, should adjust to a multi-level comprehension of the carrying capacity of the planet.
Keywords: natural environment; okolje; ecology; ekologija; globalizacija; globalization; svetovno gospodarstvo; ekonomski razvoj; onesnaževanje okolja; trajnostni razvoj; sustainable development; sonaravni razvoj